Pengaruh Temperatur Kalsinasi pada Sintesis Copper Tin Oxide (CuSnO3) Menggunakan Metode Sol-Gel - Fauzi, Muhammad; Sanjaya, Hary; Mawardi, Mawardi; Aini, Syamsi (Departemen Kimia FMIPA UNP, 2024)
Synthesis of Copper Tin Oxide (CuSnO3) was carried out using the sol-gel method with varying calcination temperatures (400; 500; 600) oC. The aim of this research is to find out how the calcination temperature affects the synthesis results of the CuSnO3 semiconductor. Then characterization was carried out using the UV-Drs instrument to obtain band gap values and SEM to determine the morphological structure. The CuSnO3 solution was made by dissolving SnCl2.2H2O and CuCl2.2H2O with a molar ratio of 1:1 in 50 mL of methanol solvent and homogenizing then adding 1 mL of the additive Diethylamine (DEA). The gel can be calcined at various temperatures to produce CuSnO3 powder. The research results explain that increasing temperature during calcination can reduce the band gap value of the synthesized CuSnO3 semiconductor material. The surface morphology of CuSnO3 powder at 1000x magnification shows clearly that the surface has cavities (hollows) with a chunk diameter of 7-11 nm.